Analiza fraktalnych właściwości polskiego rynku akcji - Kałuziak, Tomasz (Analysis of fractal properties on Polish share market, 2007)
This report is the attempt of the verification of a long-term memory of series consisting of logarithmic rate of return expanded by the research of the statistical similarity of time series on the Polish share market. It also tries to answer the questions connected with reasons of receiving dubious and ambiguous results. Showing the existence of real fractals would require the modification of currently accepted hypotheses, with the hypothesis of the effective market at the top of it, and would justify the use of opportunities, coming from the chaos theory in financial analyses. Data taken from the financial portal Money.pl come from the Stock Exchange and cover the period from October 3, 1994 (the beginning of a five-day session in a week) to January 20, 2006. The research attempt consists of the series made of 13 securities (marked on October 3, 1994) and 2 indexes. The research tries to estimate the Hurst coefficient (rescaled range analysis desribed by E. Peters) as well as the coefficient of statistical similarity (suggestedby M. Zwolankowska). Looking at the Polish share market one can clearly see the difference between the research of opportunities of the use of deterministic chaos in exact sciences, and economy which is a set of many currents and disciplines of science. The short period of functioning of the Polish Stock Exchange in Warsaw causes a lot of problems connected with the explicit identifying of fractal properties of financial series. Some estimated actual values and signals may prove the potential existence of fractal properties, but others contradict it.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 92-101